Estimate Suicidal Rate in Indonesian based on Time Window using Linear Regression - Javier Fajri Zachary; Mochammad Anshori; Wahyu Teja Kusuma (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
The global phenomenon of suicide should be a serious source of worry. Suicide rates are still relatively high in Indonesia. According to the research, there are many different reasons why people commit suicide. Anyone can commit suicide, whether they are young children, teenagers, or adults. Preventive action is one way to avoid this. The prevalence of suicide can be used to gauge the level of preventive action. You may gauge how active you are in implementing the most effective prevention by looking at the predicted suicide rate in the future. Linear regression is one technique for predicting suicide rates. The time window (tw) method is also used to prepare the data because it is in time series form. The best regression model was tw = 5 with MSE = 0.001147, RMSE = 0.033869, and R2 = 0.981643 obtained for all rates. The model with tw = 3, which has errors of MSE = 0.001547, RMSE = 0.039334, and R2 = 0.969458, is the most accurate one for the female rate. Finally, with errors MSE = 0.00318, RMSE = 0.056392, and R2 = 0.973341, we arrive at tw = 5 for the male rate